Politik Hukum Undang-Undang No 35 Tahun 2009 Tentang Narkotika Dalam Kaitannya Dengan Upaya Rehabilitasi Pecandu Narkotika - Yudhistira, Bonar; I, Ismaidar; Sembiring, Tamaulina (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Abuse narcotics increasingly day increasingly worrying . Abuse Narcotics can cause greater harm to the lives and cultural values of the nation, which will ultimately weaken national resilience. Threat abuse narcotics increasingly become the haunting specter various layer society . For That need step step strategic through formation law narcotics as well as Wrong One effort its regulated prevention in product Indonesian law , namely Invite Law No. 35 of 2009 concerning narcotics is through rehabilitation . Rehabilitation considered need as Wrong One effort recovery addict narcotics from dependence at a time prevention abuse narcotics through approach health